(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nanotechnology is a modern, technological innovation. Much study is currently under way to take more and more use of this technology. It has a lot of potential reach. Nano-particles are tiny in dimension. Nanotechnology incorporates the understanding of physics, chemistry and biology, which therefore becomes the most strong technology that can deliver a variety of facilities that render it more convenient for the living human. Nano-particles are initially defined and chemically analyzed so as to analyze the threats posed by nanotechnology. It is found that the chemical properties of substances must be known for the intent of studying the ill effects and hazards. In the current paper, the application of nano technology in electronic networks is stressed.